ANALISIS PERILAKU EKSPLORATIF DAN GROWTH MINDSET MURID SEKOLAH DASAR DALAM MEMECAHKAN MASALAH MELALUI PERMAINAN LEGO - Mona Yulia; Sutrisno, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This qualitative descriptive study aims to analyze the exploratory behavior and growth mindset profile of elementary school students while solving an authentic structural-engineering problem through lego block play. The study addresses a gap in the literature, given that most existing research on constructive block play concentrates on early childhood cognitive and social-emotional outcomes, while empirical evidence on exploratory problem-solving behavior and growth mindset among upper-grade elementary students remains limited. Six fifth-grade students were purposively selected and engaged in an individual free-construction task, followed by a collaborative “Structure Detective” mission requiring them to design a lego bridge that met defined engineering constraints. Data were collected through a five-indicator behavioral observation rubric (curiosity, fluency, flexibility, resilience, and independent trial-and-error), semi-structured interviews built on growth mindset indicators, and reflective journals, then analyzed using the Miles and Huberman interactive model with source triangulation. Findings indicate that most students displayed well-developed exploratory behavior, particularly resilience after structural collapse, and expressed beliefs consistent with a growth mindset, such as preferring challenging tasks, persisting after failure, and treating mistakes as a source of learning. Two students demonstrated exploratory behavior from the outset, three others required a brief warm-up period before engaging spontaneously, and one student displayed a mixed mindset profile that combined effort attribution with residual fixed beliefs about innate ability. The study concludes that open-ended, low-stakes lego-based engineering challenges can serve as an effective pedagogical medium for cultivating twenty-first-century problem-solving dispositions in the elementary classroom.